FORMATION OF MATHEMATICAL CONCEPTS IN PRIMARY CLASS STUDENTS - Umarova, Gozalkhon; Ismoilova, Adolatoy (University Research Base, 2024)
Education in the system today's of reforms original essence education the content of the students mastery quality and the effectiveness of s to increase directed . Uzbekistan Republic " Education - training" of the President and personnel preparation system reform to do , perfect generation adult deliver about decree and in programs mathematics of teaching quality increase with together of students thinking and personal attributes , math literacy formation and creative abilities grow up issues set given Primary mathematics course base is a natural number and zero, whole positive numbers on four arithmetic action and their main properties about sure imaginations and this to knowledge based on oral and written count methods conscious and thorough to master organize to achieve Also table cases count qualifications automatism level to be delivered organize is enough.